The contributions of the Pikler-Lóczy approach on the constitution of a pedagogy for babies: an analysis of the guiding principles - Giovanna Castro Dalledone; Ângela Scalabrin Coutinho (Universidade Federal de Santa Catarina, 2020)
The present article, result of a qualitative, aims to analyze the guiding principles of the Pikler-Lóczy approach. The corpus of research consisted of scientific papers, articles, dissertations and theses that address the topic. From the analyzed production four guiding principles were identified: 1) the deep respect for the baby and his individuality, recognizing him as a subject of rights; 2) the estimation of the baby's autonomous activity, based on its own initiatives, combined with focusing on the gradual development of autonomy; 3) the importance of the bond between the adult and the baby, based on a privileged affective relationship and in qualified moments of care; 4) the baby's freedom of movement, for playing and exploring yourself and the surroundings. It could be concluded that these principles constitute the major contribution of the pediatrician Emmi Pikler to the current Early Childhood Education, leading to a redefinition of the pedagogy for/with 0-3 years children, pointing that the pedagogical practices in this age group must be oriented by two pillars: care and relationships.